A Standard Method for Evaluating Radiocarbon Dates of Local Deglaciation: Application to the Deglaciation History of Southern Labrador and Adjacent Québec - King, George (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1985)
ABSTRACTSixty-two radiocarbon dates of marine shells, basal lake sediments, and basal peat deposits from the southeastern part of the Labrador-Ungava Peninsula, Canada, were evaluated for their accuracy and precision in estimating local deglaciation time. A procedure for the consistent evaluation of basal dates of lake sediments was developed after consideration of the problems with dating early-postglacial sediments. Of the 62 dates, 42 were selected to construct the regional déglaciation chronology, interpreted in the context of the glacial geology of the area. Late Wisconsin ice stretched to or beyond the present-day coastline throughout the study area, except in southeastern Labrador where the extreme southeastern coast was probably ice-free during Late Wisconsin time. Déglaciation began in southeastern Labrador by 13.OK. It proceeded slowly at first, and between 9.7K and 10.5K the retreating ice formed the Paradise Moraine, which parallels the southeastern Labrador coastline. In contrast, the coast at Sept-îles was not ice-free until about 9.4K. Shortly thereafter the extensive Québec North Shore Moraine System developed, although its precise age is uncertain. The position of the ice margin at 8.0K is uncertain, but may still have been near the Québec North Shore Moraine System. After 8.0K ice retreat was rapid, although extensive ice persisted at 6.5K in western Labrador and adjacent Québec. Final wastage of ice occurred in two localities in the center of the Labrador-Ungava Peninsula just after 6.OK. The precision of the well-dated glacial isochrones is estimated to be about ± 23 km.